Fructose reprogrammes glutamine-dependent oxidative metabolism to support LPS-induced inflammation - Nicholas Jones (Nature Portfolio, 2021)
Myeloid cells are able to utilize a variety of monosaccharides from our diet, including fructose. Here the authors show that when monocytes are reliant on fructose as a carbon energy source they are reprogrammed towards oxidative metabolism, glutamine anaplerosis and a pro-inflammatory phenotype owing to excess pro-inflammatory cytokine production.